PRISON, POWER AND RESISTANCE: A RESPONSE TO RAYMOND SUTTNER’S “RETHINKING AND RE-REMEMBERING PRISON” - Stevens, Garth (PINS-Psychology in Society, 2025)
Let me extend my thanks to the College of Human Sciences and also to Raymond Suttner for inviting me along to participate in this seminar today1. Before I respond to some of what has been discussed, I would like to add a single caveat. On today’s programme, I am billed as a clinical psychologist, and while this is completely accurate, I will not really be responding as a clinician, but as a social scientist more broadly. This is not to say that clinical psychology does not have anything to add to issues of violence, trauma, repression, torture, prisons, incarceration and extreme political traumatisation - indeed, some may argue that this has been its stock in trade at some points, but that this has perhaps occurred at the expense of more wide ranging, wide-angled views of these psychosocial phenomena. And so my response is far less clinical, and perhaps more open to engaging with some of the panoramic issues that lie in the background, that act as the canvass on which violence, repression and forms of resistance to them, occur - in short, some of the meta-questions.